Pendidikan Karakter Perspektif Kearifan Lokal - Ahmat, Ahmat; Barnoto, Barnoto (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Character education is an educational approach that aims to develop moral and ethical values ??in students. In addition, local wisdom is an important aspect of character education that focuses on introducing, understanding, and appreciating cultural values, customs, traditions, and community norms in the local environment. This study aims to describe Character Education from the Perspective of Local Wisdom at MI NU Miftahul Ulum Tonggowa Jatiarjo, Prigen District, Pasuruan Regency. This research is a qualitative research with a case study approach. The results of the study show that character education both inside and outside of Madrasah, teachers have tried to apply it by associating character education values ??with local wisdom. Religious character, disciplinary character, social caring character. application of the results obtained from character education from the perspective of local wisdom with several factors that can influence student character education at MINU Miftahul Ulum Tonggowa. the perspective of local wisdom, namely factors originating from the cooperation support of the madrasa, support from the authorities (Ratoh), support from parents (Bhuppa'-Bhabhu) students who are sensitive and understand this. Another factor in character education from the perspective of local wisdom is the background of the students who are Madurese, in practice there is still a lack of supervision from the teacher, more and more of the younger generation are working outside, the value of local wisdom in the family has been lost.